An easy tool to assess ventilation in health facilities as part of air-borne transmission prevention: a cross-sectional survey from Uganda - Brouwer, Miranda; Katamba, Achilles; Tebasoboke Katabira, Elly; Leth, Frank van (BMC Infectious Diseases, 2017)
No guidelines exist on assessing ventilation through air changes per hour (ACH) using a vaneometer. The objective of the study was to evaluate the position and frequency for measuring air velocity using a vaneometer to assess ventilation with ACH; and to assess influence of ambient temperature and weather on ACH. Methods: Cross-sectional survey in six urban health facilities in Kampala, Uganda. Measurements consisted of taking air velocity on nine separate moments in five positions in each opening of the TB clinic, laboratory, outpatient consultation and outpatient waiting room using a vaneometer. We assessed in addition the ventilation with the “20% rule”, and compared this estimation with the ventilation in ACH assessed using the vaneometer. Results: A total of 189 measurements showed no influence on air velocity of the position and moment of the measurement. No significant influence existed of ambient temperature and a small but significant influence of sunny weather. Ventilation was adequate in 17/24 (71%) of all measurements. Using the “20% rule”, ventilation was adequate in 50% of rooms assessed. Agreement between both methods existed in 13/23 (56%) of the rooms assessed. Conclusion: Most rooms had adequate ventilation when assessed using a vaneometer for measuring air velocity. A single vaneometer measurement of air velocity is adequate to assess ventilation in this setting. These findings provide practical input for clear guidelines on assessing ventilation using a vaneometer. Assessing ventilation with a vaneometer differs substantially from applying the “20% rule”.
Keywords: Ventilation; Infection control; Tuberculosis